2001
DOI: 10.1046/j.1523-1755.2001.059002693.x
|View full text |Cite
|
Sign up to set email alerts
|

Familial nephropathy differing from minimal change nephropathy and focal glomerulosclerosis

Abstract: We propose that this family represents a new familial nephropathy. The molecular basis of the permeability defect remains to be identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 34 publications
2
21
0
Order By: Relevance
“…These results are compatible with the entity referred to as "no change disease" previously described in experimental models and in cases of human nephrotic syndrome (25)(26)(27).…”
Section: Renal Phenotyping Of P0 ϫ/ϫ Micesupporting
confidence: 91%
See 1 more Smart Citation
“…These results are compatible with the entity referred to as "no change disease" previously described in experimental models and in cases of human nephrotic syndrome (25)(26)(27).…”
Section: Renal Phenotyping Of P0 ϫ/ϫ Micesupporting
confidence: 91%
“…Even if most proteinuric renal diseases are associated with massive loss of podocyte foot processes, there are indeed human and experimental models of nephrotic-range proteinuria in which this podocyte abnormality is absent. In human, a familial form of nephrotic syndrome without podocyte alteration has been previously reported (25), and a sporadic case of massive proteinuria with only segmental effacement of foot processes affecting 20 to 30% of capillary loops has been observed (26). In the rat, injection of mAb 5-1-6 directed against nephrin induces massive proteinuria without any foot process damage (27).…”
Section: Discussionmentioning
confidence: 99%
“…14 Renal biopsies from patients with minimal change nephropathy show absent or markedly reduced glomerular basement membrane staining with an antibody against heparan sulfate side chains but normal staining for the agrin core protein of heparan sulfate proteoglycans. 15 Recently, it has been demonstrated that relapsing steroid-sensitive nephrotic syndrome in children is associated with elevated urinary heparanase activity, 16 implicating loss of heparan sulfate in the pathogenesis of the nephrotic syndrome in these patients. Heparanase is expressed by peripheral T lymphocytes, providing a link between the immune abnormalities and glomerular basement membrane changes observed in minimal change nephropathy.…”
Section: Hereditary Multiple Exostosesmentioning
confidence: 99%
“…Variants of minimal-change nephritic syndrome with proteinuria are not associated with podocyte foot process effacement (44). Branten et al (45) report that a familial form of nephrotic syndrome occurs in the absence of podocyte foot process effacements. Additionally, several other anecdotal reports with human biopsies that support the notion that proteinuria can occur without podocyte foot process effacement exist.…”
mentioning
confidence: 99%